The Tunisian Introduction to Knowing Faith and Islam by Imam Abu Ishaq al-Tunisi Al-Maliki (d.1266 AH) ) from the beginning of the manuscripts.... until he said: “He is upon the light of his Lord” ( a study to follow (Islamic Sciences Journal, 2024)
ABSTRACTThe investigation of the manuscript included clarifying important matters, the first of which was the reason for writing the manuscript, which was the answer to a question that some people asked the author, which was about Islam and faith, are they created or not? The author responded to this by explaining the origin of faith, and that it is not created in its origin, but its branch - which is deeds - were created by God Almighty and acquired for His servants. Then the author went on to provide a comprehensive explanation of the meaning of Islam, its conditions, and the fulfillment of its obligations, and he provided clarification of the relationship between Islam and faith and explained their requirements.After that, the author followed the traditions of previous scholars in explaining the principles of religion in speaking about the oneness of God Almighty, and what is obligatory, permissible, and impossible in relation to God Almighty of attributes and actions. He also did this in explaining what is obligatory, permissible, and impossible in relation to the Messengers, peace and blessings be upon them, and then he expanded the discussion on The rationale for faith and Islam, mentioning the rules of Islam, its branches and laws, and explaining matters of religion and the place of Islam.
Keywords: Doctrine, Islam, Faith, Allah, Messengers.